Perancangan Jaringan LAN Pada Gedung Baru SMK Muhammadiyah Purwodadi Dengan Metode Waterfall Menggunakan Software Cisco Packet Tracer - Singgih Arif Widodo (Universitas Muhammadiyah Purworejo, 2019)
The new building of Muhammadiyah Purwodadi High School has no wireless LAN (Local Area Network). So the teachers and employees at the office have no mutually inter-connected parts. For sure this is very inflexible and would also interfere with the convenience of the mobility of these employees. The purpose of making the design of wireless LAN networks is the solution to resolve the problems that exist in the new building of Muhammadiyah Purwodadi High School. The method used is the Waterfall method and software Cisco Packet Tracer. Stages of the Waterfall method approach consisting of analysis, system design, implementation, testing, and system maintenance. The result of the design of wireless LAN in the new building of Muhammadiyah Purwodadi High School arranged systematically to help the performance of the servicemembers to be more effective and efficient.